Reversibility of functional deficits in experimental models of Rett syndrome. (22nd March 2010) - Cobb, Stuart; Guy, Jacky; Bird, Adrian
Abstract : Mutations in the X-linked MECP2 gene are the primary cause of the severe autism spectrum disorder RTT (Rett syndrome). Deletion of Mecp2 in mice recapitulates many of the overt neurological features seen in humans, and the delayed onset of symptoms is accompanied by deficits in neuronal morphology and synaptic physiology. Recent evidence suggests that reactivation of endogenous Mecp2 in young and adult mice can reverse aspects of RTT-like pathology. In the current perspective, we discuss these findings as well as other genetic, pharmacological and environmental interventions that attempt phenotypic rescue in RTT. We believe these studies provide valuable insights into the tractability of RTT and related conditions and are useful pointers for the development of future therapeutic strategies.